2002
DOI: 10.1097/00000539-200209000-00007
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacokinetics and Tolerability of an Intravenous Infusion of the New Hydroxyethyl Starch 130/0.4 (6%, 500 mL) in Mild-to-Severe Renal Impairment

Abstract: Dependency of the pharmacokinetics of hydroxyethyl starch 130/0.4 on renal function was studied. The area under the time concentration curve increased moderately with more severe renal dysfunction; however, small plasma concentrations were observed after 24 h. Terminal half-life and peak concentration remained unaffected by renal impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 23 publications
2
49
0
3
Order By: Relevance
“…Thus, the present study did not demonstrate that in patients with abnormal kidney function, volume replacement strategy using gelatin or HES 130/0.4 does not negatively affect renal function. However, in a study in volunteers with mild-to-moderate kidney dysfunction, infusion of 500 ml of HES 130/04 was not associated with a further deterioration in kidney function (e.g., unchanged creatinine clearance) [29].…”
Section: A R T I C L Ementioning
confidence: 85%
“…Thus, the present study did not demonstrate that in patients with abnormal kidney function, volume replacement strategy using gelatin or HES 130/0.4 does not negatively affect renal function. However, in a study in volunteers with mild-to-moderate kidney dysfunction, infusion of 500 ml of HES 130/04 was not associated with a further deterioration in kidney function (e.g., unchanged creatinine clearance) [29].…”
Section: A R T I C L Ementioning
confidence: 85%
“…Some reports have shown that HES has no adverse infl uence on renal function in surgical patients [19,20], while other reports have shown that HES may impair renal function in surgical patients [21,22]. A recent review suggested that HES may have adverse effects on renal function, regardless of its molecular weight, DS, or C2/C6 ratio [23].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, HES 130/0.4 did not negatively influence kidney integrity compared with a human albuminbased volume-replacement strategy in patients who had undergone cardiac surgery [97] or aortic aneurysm surgery [105] with preoperative compromised kidney function. In cases of severe renal dysfunction, a single bolus of 500 ml HES 130/0.4 did not impair creatinine clearance either [106]. Any hyper-oncotic colloid may have the potential to produce kidney dysfunction or renal failure because colloids may decrease glomerular filtration [13].…”
Section: Renal Functionmentioning
confidence: 94%